The Autocephalous Structure of the Orthodox Church in a Historical – Canonical Perspective - Yovchev, Ivan (Studia Ceranea, 2025)
It is well known that the foundations of Church organization were established by the Holy Apostles themselves, who were the first to spread the teachings of Christ. They fulfilled this mission in accordance with the command of the Lord Jesus Christ (Matt. 28:18–19), as they traveled to various regions to establish Christian communities. Initially, each Christian community, led by its bishop, constituted a distinct ecclesiastical unit, which may be regarded as the prototype of the modern local autocephalous Churches. The existence of multiple, distinct, and independent local Churches does not hinder conciliarity within the Church. On the contrary, the major issues concerning the life of the entire Church were historically resolved through conciliar processes. With the recognition of Christianity as a legally equal religion under Emperor Constantine the Great, the organization of Church dioceses began to mirror the administrative divisions of the Roman Empire. By the 4th century, this alignment was fully realized. In the centuries that followed, the structuring of local Churches developed gradually, shaped by historical circumstances.